Complexidade e ciberjornalismo: as práticas jornalísticas na era da informação - Viana, Bruno (2017)
With the advent of network societies, the social, economic and political changes have been intensified, mainly by technological innovations, which now permeate all spheres of society. Journalism is not left out of this phenomenon. The current age of information is as technology-based, works in a logical network, a dynamic logic and complex at the same time. This article intends to reflect on how journalism produced for digital platforms, is in the midst of the complexity of the information society. From the approaches introduced by the paradigms of complexity and Informationalism, here it is looking to discover through the theme of the literature review, which new journalistic practices in the field of online journalism, are being used. The methodology used was the bibliographical research.